Relationship between microalbuminuria and renal dysfunction in essential hypertension - (:unkn) unknown (My University, 1998)
Objective: Microalbuminuria has been reported to vary between 10-30% in essential hypertension (EH) and to be associated with increased cardiovascular (CV) mortality and morbidity. A cohort of 250 patients with essential hypertension were studied for the prevalence of microalbuminuria and its association with other target organ damage. Subjects and Methods: All patients had never been treated for hypertension or had been taken off therapy at least four weeks prior to study. After a negative urine culture was obtained, 24-hour samples of urine for measurement of urinary albumin excretion (UAE) were taken. If at least two out of three measurements of UAE were between 30-300 mg/day, the patient was qualified as having microalbuminuria. Each patient underwent an evaluation including previous medical history, physical examination, urinalysis, chest roentgenogram, electrocardiogram, fundoscopic examination by ophthalmologist, and blood studies for electrolytes, creatinine, plasma lipids and the measurement of urinary sodium, albumin and creatinine. At the end of study period patients were divided into three groups according to the level of urinary albumin excretion (UAE): Group A with UAE < 20 mg/day, group B with UAE between 20 and 28 mg/day and group C with UAE > 28 mg/day. The cutoff points of 20 and 28 mg/day were chosen according to the 75th and 95th percentiles of our normal values. Results: The three groups were similar in age, body mass index (BMI), duration of hypertension acid serum lipid levels. Diastolic blood pressure (DBP), mean arterial blood pressure (MABP) and serum creatinine were significantly higher in group C when compared to group A (p < 0.01). When stepwise multiple regression analysis was performed, serum creatinine level (F = 18.84, P < 0.001), DBP (F = 17.08, P < 0.001) and retinopathy (F = 16.25, P < 0.001) appeared as the significant but weak predictors of microalbuminuria accounting for the 7%, 11% and 11% of its variance respectively. Conclusion: This study confirms the relationship between blood pressure levels and development of increased UAE in the early phase of hypertension. There is an important correlation between serum creatinine level and microalbuminuria highlighting its potential role in the development of renal damage in hypertension as well as its potential importance as an early marker of both renal and vascular damage in essential hypertension.
Keywords: Essential hypertension; Microalbuminuria; Target-organ damage